(N|LEKTROMAGNITNYE \FFEKTY W TWERDYH TELAH (B/s - (NnOWACKIJ(B, (NwITOLXDs; (N{A^NEW(B, (Nw(B.(Na(B.s; (N{APIRO(B, (Ng(B.(Ns(B.s ((NmOSKWA (B:s (NmIR(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 155-157 (62 (NNAZW(B.)s
(NbIBLIOGR(B.: (NS(B. 155-157s
Keywords: (NpXEZO\LEKTRI^ESTWOs; (NmAGNITOUPRUGOSTXs